Politik Hukum Pemilu Di Indonesia: Pergeseran Dari Rule By Law Menuju Rule Of Law Dalam Konfigurasi Politik Dan Demokrasi Substantif - Nurhakim, Irfan; Nurul Huda, Uu (Sharia Journal and Education Center Publishing, 2025)
The transformation of Indonesia’s electoral legal politics reflects a long trajectory from authoritarianism toward a more open democracy. This article examines how electoral law functions within shifting political configurations from the Old Order to the 2024 general election. The study aims to analyze the transformation of legal politics from rule by law to rule of law, focusing on the influence of political configuration on electoral legislation and administration. This research employs a normative, historical-descriptive, and philosophical approach, integrating Mahfud MD’s theory of political configuration, Lawrence M. Friedman’s legal system framework, and the concepts of substantive democracy and institutional authoritarianism. The findings reveal that the transformation of electoral legal politics directly correlates with changes in political power which is before reform, electoral law served as an instrument of authority; the transitional period marked the rise of independent institutions; and the reform consolidation era demonstrated procedural progress yet lacked substantive democracy. The novelty of this study lies in its integrative historical-periodization analysis that connects legal and political dimensions to assess the direction of Indonesia’s post-2024 electoral democracy. Keywords: electoral law, legal politics, political configuration, rule of law, substantive democracy.